Exploring and understanding careers in criminal justice : a comprehensive guide - Sheridan, Matthew J., 1948-; Rainville, Raymond R., 1943- (Lanham : Rowman & Littlefield, 2016)
This book explores the criminal justice career landscape by providing a glimpse into the different criminal justice careers and provides advice as to how to prepare to enter those career fields. This book includes personal profiles that exemplify real work in the criminal justice profession; these have been written by current employees, some retired and some by exemplary leaders in the field.
Introduction: Why Another Book on Criminal Justice Careers? -- Exploring Careers in Criminal Justice -- Careers in Law Enforcement -- Careers in Corrections -- The Courts, Its Actors, and Its Functions -- The Federal Government -- Getting the Job, Entering the Field, and Career Advancement -- Criminal Justice Ethics -- Life after the Career, or "I Can't Live on That!"
Includes bibliographical references (pages 279-282) and indexes.
Keywords: Criminal justice, Administration of -- Vocational guidance -- United States; Law enforcement -- Vocational guidance -- United States